Contributions of Didactic Engineering and the technique of tiling in the development of a course aimed at undergraduate students in Mathematics (Research, Society and Development, 2021)
This work is an excerpt from a master's research that is linked to the project entitled “Mathematical and Interdisciplinary Investigations in Learning Projects”. This research reports the development of a course conceived during the COVID19 pandemic and, for this reason, structured in a virtual environment, with remote activities in Geogebra Book software and synchronous in Google Meet. The purpose of the course is to encourage ways to explore principles and generalization of patterns from the composition of polygons in the plane through the technique of tiling. The target audience is academics from the undergraduate mathematics course enrolled in the sixth semester of the course. The objective of the article is to analyze the performance of 2 academics when submitted to a tiling activity through a didactic engineering. The theoretical-methodological-conceptual conception is Didactic Engineering, through which the following phases were developed: previous analyses; design and a priori analysis; experimentation, a posteriori analysis and validation. The results showed that E.D. contributed to the expansion and construction of geometric mathematical knowledge, as it was possible to detect that academics understand in a contextualized way the relationship between elements of a regular polygon and their application in the tiling technique, as well as being able to make conjectures and generalizations representable through of statements and formulas.